Screening of compound-formulated Bacillus and its effect on plant growth promotion - Shen, Yuying; Yang, Huan; Lin, Zheng; Chu, Linglong; Pan, Xiao; Wang, Yu; Liu, Wenbo; Jin, Pengfei; Miao, Weiguo (Frontiers in Plant Science, 2023)
Bacillus bacteria can produce abundant secondary metabolites that are useful for biocontrol, especially in maintaining plant root microecology, and for plant protection. In this study, we determine the indicators of six Bacillus strains for colonization, promotion of plant growth, antimicrobial activity, and other aspects, with the aim of obtaining a compound bacteriological agent to construct a beneficial Bacillus microbial community in plant roots. We found that there was no significant difference in the growth curves of the six Bacillus strains over 12 h. However, strain HN-2 was found to have the strongest swimming ability and the highest bacteriostatic effect of n-butanol extract on the blight-causing bacteria Xanthomonas oryzae pv. oryzicola. The hemolytic circle produced by the n-butanol extract of strain FZB42 was the largest (8.67 ± 0.13 mm) and had the greatest bacteriostatic effect on the fungal pathogen Colletotrichum gloeosporioides, with a bacteriostatic circle diameter of 21.74 ± 0.40 mm. Strains HN-2 and FZB42 can rapidly form biofilms. Time-of-flight mass spectrometry and hemolytic plate tests showed that strains HN-2 and FZB42 may have significantly different activities because of their ability to produce large quantities of lipopeptides (i.e., surfactin, iturin, and fengycin). Different growth-promoting experiments revealed that the strains FZB42, HN-2, HAB-2, and HAB-5 had better growth-promoting potential than the control, and therefore these four strains were compounded in an equal ratio and used to treat pepper seedlings through root irrigation. We found an increase in the stem thickness (13%), leaf dry weight (14%), leaf number (26%), and chlorophyll content (41%) of pepper seedlings treated with the composite-formulated bacterial solution compared to the optimal single-bacterial solution treatment. Furthermore, several of these indicators increased by an average of 30% in the composite solution-treated pepper seedlings compared with the control water treatment group. In conclusion, the composite solution obtained by compounding strains FZB42 (OD600 = 1.2), HN-2 (OD600 = 0.9), HAB-2 (OD600 = 0.9), and HAB-5 (OD600 = 1.2) in equal parts highlights the advantages of a single bacterial solution, which includes achieving good growth promotion and antagonistic effects against pathogenic bacteria. The promotion of this compound-formulated Bacillus can reduce the application of chemical pesticides and fertilizers; promote plant growth and development; avoid the imbalances of soil microbial communities and thus reduce the risk of plant disease; and provide an experimental basis for the production and application of various types of biological control preparations in the future.